RECTEMA (Recount Text Maze): An Educational Game to Facilitate Reading Recount Text - Aldian Fatka Arsandy; Astried Damayanti (STKIP PGRI Trenggalek, 2021)
The objective of this research was to develop RECTEMA (Recount Text Maze): an educational game to facilitate the eighth-grade students of SMPN 1 Suruh in reading recount text. The design of this research was R&D which aims to develop learning products and is equipped with quasi-experimental to test the effectiveness of these products. The sample of this study was class VII students at SMPN 1 Suruh for the academic year 2020/2021 which consisted of 17 students in class A and 17 students in class B. The instruments used in this study were questionnaires and interviews. The results of the questionnaire data were analyzed quantitatively. Meanwhile, the results of the interview data were analyzed qualitatively. This learning product was developed through 5 stages, namely needs analysis based on student needs, theories related to products, product development, evaluation of product results by experts, and product testing in the field. This study uses the assistance of SPSS 25 to process the data that has been collected and the results of the t-test sig. 2 tailed is 0.000 (<0.05), this means there is an effect between the experimental group and the control group. Based on the explanation above, RECTEMA (Recount Text Maze) is an effective product as a learning medium for recount text